2020
DOI: 10.1177/1945892420945218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Post-Surgical Therapies on Endoscopic and External Dacryocystorhinostomy: Systematic Review and Meta-Analysis

Abstract: Background Epiphora is a common ophthalmologic sign that is most commonly caused by distal acquired lacrimal obstruction. Recent data have demonstrated that external dacryocystorhinostomy (EXT-DCR) and endoscopic endonasal dacryocystorhinostomy (END-DCR) can be considered the treatments of choice. However, different post-surgical medical therapies are available and are currently used to improve surgical outcomes, although no direct comparison has been performed. Objective To analyse the influence of post-surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Following proper treatment, several post-surgical medical therapies are available, and, seem particularly useful in case of non-oncologic DALO. However, with the available data, the actual influence of adjunctive medical therapies is difficult to demonstrate 31 , and endoscopic visualization of the healing process associated with nasal medication Figure 2. Endoscopic dacryocystorhinostomy surgical procedure.…”
Section: Post-surgical Management and Follow-upmentioning
confidence: 99%
“…Following proper treatment, several post-surgical medical therapies are available, and, seem particularly useful in case of non-oncologic DALO. However, with the available data, the actual influence of adjunctive medical therapies is difficult to demonstrate 31 , and endoscopic visualization of the healing process associated with nasal medication Figure 2. Endoscopic dacryocystorhinostomy surgical procedure.…”
Section: Post-surgical Management and Follow-upmentioning
confidence: 99%
“…Finally, considering post-surgical therapy, different possibilities have been discussed in the literature, both for postoperative medical therapy and bicanalicular stenting. Nevertheless, with the current data available regarding END-DCR, no difference is noted regarding either lacrimal stenting [34][35][36] or medical therapies (e.g., mitomycin C, oral antibiotics (ABT), nasal steroids or ocular steroids) [37][38][39][40]. As a result, in our series, we do not apply mitomycin C, but we do prescribe post-operative oral ABT and antibiotic-steroid eye drops; bicanalicular stenting was placed in only selected patients (2/14) in which extensive fibrosis was noted as failure of the primary surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that are impactful in the realm of endoscopic surgery, includes a cadaver study by Li et al 14 on surgical techniques to access the medial intraconal space (MIS) and a meta-analysis by Vinciguerra, et al 15 on two treatments options for Epiphora: external vs endoscopic approaches. In the first study, Li et al 14 compared the advantage and disadvantage of transethmoidal and prelacrimal approaches to access the medial intraconal space (MIS), and reported that while both approaches are capable to assess MIS, each approach has its own advantages for assessing different zones within the MIS.…”
Section: Head Neck Cancer and Endoscopic Surgerymentioning
confidence: 99%
“…In the first study, Li et al 14 compared the advantage and disadvantage of transethmoidal and prelacrimal approaches to access the medial intraconal space (MIS), and reported that while both approaches are capable to assess MIS, each approach has its own advantages for assessing different zones within the MIS. The 2nd study 15 attempted to examine different post-surgical medical therapies that may improve surgical outcomes of external dacryocystorhinostomy (EXT-DCR) and endoscopic endonasal dacryocystorhinostomy (END-DCR). Limited analyses showed that nasal steroids, oral antibiotics nasal decongestant and silicone stenting may have no meaningful influence.…”
Section: Head Neck Cancer and Endoscopic Surgerymentioning
confidence: 99%
See 1 more Smart Citation